The myth of perpetual summer - Crandall, Susan (New York : Gallery Books, 2018)
"A girl uncovers her family's history of mental illness against the background of the Civil Rights Movement and the Vietnam War in this moving coming-of-age tale that harkens to both The Glass Castle and Forrest Gump. Tallulah James comes from a long line of intelligent college professors with strong Southern roots...and long-buried family secrets. Tallulah's childhood is a tumultuous one. Her mother is often absent as she puts her goals to save the world over her family. Her father's ignored bipolar disorder results in bouts of depression and manic behavior that often leave Tallulah afraid and confused. But with her older brother Grif to watch out for her and her grandmother to make sure she grows up into a proper Southern lady--whatever that means--her life is stable enough: that is, until a terrible tragedy rocks her entire community. Forced to move away from everyone she knows and loves at the age of sixteen, Tallulah lives on her own for seven years before returning back to the Mississippi town where it all began. As she begins to uncover her family history and to forgive them for the past, she finally learns the truth that has been hidden from her for so long. In this heartwrenching, raw, and ultimately satisfying novel set against the background of the 1960s, the award-winning author of Whistling Past the Graveyard explores what the word family really means: in all of its ugliness, beauty, and messy complications"--
Keywords: Nineteen sixties -- Fiction; Family secrets -- Fiction; FICTION / Coming of Age; FICTION / Historical; Domestic fiction; Coming of age fiction